Ikhtilaf para ulama mengenai pembelian makanan melalui go-food - Pratama, Agil Herlan (Maliki Interdisciplinary Journal, 2025)
The Go-Food service allows users to order food from restaurants using the Go-Jek application. However, opinions on the permissibility of Go-Food transactions vary. Some scholars prohibit this transaction based on the hadith of the Prophet, but other scholars allow it on the grounds of a service rental transaction. However, there are efforts to calm customers but remain within the corridor of sharia. This study aims to examine the differences of several scholars regarding purchasing food through Go-Food. To collect information from various sources and use qualitative data analysis techniques, this study combines a qualitative approach with a literature review. Based on the results of the study, there are differences of opinion on how to interpret the hadith of the Prophet Muhammad SAW regarding the law of transactions due to the practice of ordering food through the Go-Food service. Ustadz Ammi Nur Baits stated that Go-Food transactions are haram because there are two or more contracts in the transaction. However, he emphasized the need for a deeper investigation into the Go-Food transaction procedure. On the other hand, Muhammad Syamsudin assured that Go-Food transactions are valid and permissible, because all parties involved understand the transaction. According to Buya Yahya and Ustad Dr. H. Sutisna, MA, this service is in accordance with current developments and does not violate Islamic rules, as long as it does not violate Islamic law, transactions using Go-Food and Go-Pay are permitted.